Sikap Bertanggung Jawab Sebagai Bagian Dari Pendidikan Karakter Pada Film Animasi How To Train Your Dragon 3 The Hidden Word Dan Tinker Bell And The Lost Treasure - Maharani Eka Saputri; Binti Maunah (The Elementary Journal, 2023)
Film is a medium that still exists and is used to convey a message. Films also influence audiences so that they create depictions that change people's thinking patterns. This research discusses the value of responsibility as part of character education in the animated films How To Train Your Dragon 3 The Hidden Word and Tinker Bell And The Lost Treasure. In both animated films, they tell stories about action and adventure that contain and display an attitude of responsibility.This research aims to (1) Explain the characteristics of the main characters in the animated films How to Train Your Dragon 3 the Hidden Word and Tinker Bell and The Lost Treasure, (2) Explain what attitudes of responsibility are contained in the animated films How to Train Your Dragon 3 the Hidden Word and Tinker Bell and The Lost Treasure are seen from the indicator of the value of responsibility. The approach uses library research, the method used in analyzing is the content analysis method with data collection techniques by means of observation and documentation (observing the films How To Train Your Dragon 3 The Hidden Word and Tinker Bell And The Lost Treasure). Based on data analysis, it was found that the attitude of responsibility seen in terms of the indicators of responsibility found and obtained in this research include: (1) doing what is expected (should) be done. (2) Future plans. (3) Be persistent and always try. (4) Discipline yourself. (5) Think before acting. (6) Set a good example for others. (7) Responsible for words, (8) Responsible for actions and attitudes